The lady and the highwayman - Hough, John, 1941-; Fennell, Albert; Grant, Hugh.; Samms, Emma.; Reed, Oliver, 1938-1999.; York, Michael; Morley, Robert; Mills, John, 1908-2005.; Cartland, Barbara, 1902-2000; Grade Company; Platinum Disc Corporation (LaCrosse, WI : Platinum Disc Corp., 2004)
Seventeenth century adventure of an English aristocrat (Grant) who is forced to become a highwayman.
Based on the novel by Barbara Cartland.
Emma Samms, Oliver Reed, Claire Bloom, Christopher Cazenave, Lysette Anthony, Hugh Grant, Michael York, John Mills, Ian Bannen, Robert Morley, Bernard Miles, Gordon Jackson, Gareth Hunt.
Keywords: Feature films; Adventure films